The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s43042-022-00246-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphism in Madura pregnant women with hypertension: a case control study

Abstract: Background Genetic factors are important considerations in the etiology of preeclampsia and gestational hypertension. Several previous studies have shown an association of Vitamin D receptor (VDR) gene polymorphisms with hypertension in pregnancy. However, the number of studies is still very limited and the results differ from one another. Aim of the study This study aimed to analyze the polymorphisms of rs2228570 and rs731236 of the VDR gene in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In the present study, approximately 6 (67%) studies used PCR-RFLP (26, 27,42,44,45,47). All studies that utilized PCR-RFLP demonstrated an association with FokI and were reported from Asian populations (27,42,44). In contrast, one study reported an association with the ApaI variant (45).…”
Section: Association Of Vdr Gene Variants With Hdp Detected Using Dif...mentioning
confidence: 64%
See 4 more Smart Citations
“…In the present study, approximately 6 (67%) studies used PCR-RFLP (26, 27,42,44,45,47). All studies that utilized PCR-RFLP demonstrated an association with FokI and were reported from Asian populations (27,42,44). In contrast, one study reported an association with the ApaI variant (45).…”
Section: Association Of Vdr Gene Variants With Hdp Detected Using Dif...mentioning
confidence: 64%
“…According to our based on population, 4 (44%) studies that showed an association with the FokI variant were reported in Asian populations (27,42,44,46). However, one study of Caucasians in Italy reported an association with the combined variant of FokI and BsmI (43).…”
Section: Association Of Vdr Gene Variants With Hdp In the Studied Pop...mentioning
confidence: 92%
See 3 more Smart Citations